2019
DOI: 10.1002/jmri.27024
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Novel Multiparametric MRI Radiomic Nomogram for Preoperative Evaluation of Early Recurrence in Resectable Pancreatic Cancer

Abstract: BackgroundIn pancreatic cancer, methods to predict early recurrence (ER) and identify patients at increased risk of relapse are urgently required.PurposeTo develop a radiomic nomogram based on MR radiomics to stratify patients preoperatively and potentially improve clinical practice.Study TypeRetrospective.PopulationWe enrolled 303 patients from two medical centers. Patients with a disease‐free survival ≤12 months were assigned as the ER group (n = 130). Patients from the first medical center were divided into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 40 publications
3
50
1
Order By: Relevance
“…As regards the use of MR imaging for treatment response prediction, the main experiences were focussed on the radiomic analysis of MR images acquired at a single time point: Kaissis et al proposed a model able to predict the overall survival by analysing the pre-operative diffusion weighted images, while Tang et al elaborated a model for early recurrence prediction from the analysis of pre-operative T2 and T1-weighted MR images [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…As regards the use of MR imaging for treatment response prediction, the main experiences were focussed on the radiomic analysis of MR images acquired at a single time point: Kaissis et al proposed a model able to predict the overall survival by analysing the pre-operative diffusion weighted images, while Tang et al elaborated a model for early recurrence prediction from the analysis of pre-operative T2 and T1-weighted MR images [ 44 , 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Participants received 12 weekly cycles of paclitaxel alone (standard of care) or in combination with one of nine experimental agents, followed by four cycles of anthracycline-cyclophosphamide (AC) every 2–3 weeks, prior to definitive surgery (Fig. 4 ) 10 . Patients with HER2-positive cancer also received trastuzumab for the first 12 cycles.…”
Section: Methodsmentioning
confidence: 99%
“…All patients provided written informed consent to participate in the study. Subsets of the patient cohort were included in previous studies 10 , 26 , 27 .
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, radiomics‐related studies on MRI of pancreatic tumors are limited. However, there are still a few ambitious reports, such as the study on the differentiation of pNETs from adenocarcinoma, or preoperative evaluation of early recurrence in resectable pancreatic cancer 9,10 . Bian et al successfully reported on the classification of G1 vs. G2/3 of pNETs by MRI radiomics; however, the distinction between pNET Grade 3 and NEC is also clinically relevant, because the prognosis differs significantly between them.…”
mentioning
confidence: 99%